Bonding characteristics between carbonized copper and a glass/phenolic composite. (1st July 2016) - Oh, Seungjin; Kim, Minkook; Choe, Jaeheon; Lee, Dai Gil
Abstract: Sandwich constructions composed of aluminum faces and a polymeric foam core generally have been used for thermal insulation structures for buildings. However, when fires occur, these sandwich constructions fail easily due to their low mechanical strength at high temperature and generate toxic gases during burning. Therefore, phenolic resin composites have been tried recently for fire retarding structures because of their low smoke generation level and good fire resistance due to the char generation on its surface. In this study, copper foil was adhesively bonded to glass/phenolic composite faces to develop a fire retardant sandwich construction. To improve the adhesive bonding strength between the copper foil and the glass/phenolic composite, the carbonized layer method was developed. The pre-cured phenolic resin was carbonized and used as a primer. Finally, an optimum treatment condition of the carbonized layer method for the copper foil and glass/phenolic composite was investigated.